The reality of ethical finance in the active commercial banks in Algeria A case study of a sample of banking agencies in Bordj Bou Arreridj and Setif - ريغي أسماء; قايدي خميسي (Finance and Business Economies Review, 2021)
Through this study, we aim to know the reality of the Algerian commercial banks ’adoption of ethical financial dimensions and principles, through a field study of twenty-four active banking agencies in the states of Bordj Bou Arreridj and Setif, then doing a statistical treatment of the information and data obtained using the SPSS program and analyzing it economically This research reached a set of results, which are the complete absence of an ethical financial culture in commercial banks active in Algeria. There are some governmental banks that participate in social projects, but its contribution remains limited and falls within the implementation of the directives of the Central Bank and its monetary policy, and not for adopting the dimensions and principles of ethical finance.